PERBANDINGAN BENTUK -TE IRU DAN -TSUZUKERU SEBAGAI PEMARKAH ASPEK IMPERFEKTIF DALAM BAHASA JEPANG - Elizabeth Ika Hesti Nindya (KIRYOKU, 2017)
-Te iru and -tsuzukeru form are both  express the imperfective aspect. Although they both show the continuity of the situation but  the situations they exhibit are not exactly the same. In terms of its form       -te iru is hojodoushi, while -tsuzukeru is fukugoudoushi. In terms of the meaning, -te iru states the meaning of progressive aspects, habituatif, resultatif, keiken, kiroku, kanryou, while the -tsuzukeru expresses the meaning of continuous, and resultatif.